The therapist [large type] - Paris, B. A. (Wheeler Publishing large print hardcover, 2021)
"When Alice and Leo move into a newly renovated house in The Circle, a gated community of exclusive houses, it is everything they've dreamed of. But appearances can be deceptive.... As Alice is getting to know her neighbors, she discovers a devastating secret about her new home, and begins to feel a strong connection with Nina, the therapist who lived there before. Alice becomes obsessed with trying to piece together what happened two years before. But no one wants to talk about it. Her neighbors are keeping secrets and things are not as perfect as they seem..."--Page 4 of cover.